Pameran RASA 2013 = RASA showcase 2013 / Wan Nur Khalisah Shamsudin...[et.al] - Shamsudin, Wan Nur Khalisah; Mohd Radzuan, Lili Eliana (Faculty of Art and Design, Universiti Teknologi MARA Melaka, Alor Gajah Campus, 2014)
Digital Art is a form of art that uses computer software to perform various technique such as manipulation, illustration, modification and many more. RASA is a digital art design showcase participated by 17 lecturers from Graphic Design & Digital Media Program. under the Faculty of Art & Design. UiTM Melaka. 17 artworks were displayed in art Gallery Pakus Halus. Bandar Hilir a modern and contemporary art gallery located in the heart of Melaka Historical City.